Cardiac Cell and Gene Transfer - Metzger, Joseph M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2003)
Cellular and gene-based experimental techniques promise powerful new therapeutic agents for the remediation of both acquired and inherited cardiovascular disease. In Cardiac Cell and Gene Transfer: Principles, Protocols, and Applications, Joseph M. Metzger and a panel of leading scientific experts detail many novel techniques and strategies for the cellular and genetic modification of heart function. These highly experienced authors provide step-by-step protocols for vector production and purification, for gene and cell delivery techniques, and for physiological assessment in vivo and in vitro. Timely, authoritative, and state-of-the-art, Cardiac Cell and Gene Transfer: Principles, Protocols, and Applications constitutes an invaluable guide to all the new cellular and gene-based technologies needed by basic and clinical investigators working to illuminate today's unanswered questions about heart disease and ultimately to improve the heart performance in all their patients.
Vectors for Cardiac Gene Transfer -- Adenoviral Vectors -- Gutted Adenoviral Vectors for Gene Transfer to Muscle -- Dual Vector Expansion of the Recombinant AAV Packaging Capacity -- Lentivirus Vector-Mediated Gene Transfer to Cardiomyocytes -- Cell Transfer to Myocardium -- Cell Therapy in the Heart -- Cardiac Cell Transplantation -- Cell Grafting for Cardiac Repair -- Vectors for Cardiac Gene Transfer -- Suppressor tRNAs -- Antisense Oligonucleotides -- Theoretical and Technical Considerations for Gene Transfer into Vascularized Cardiac Transplants -- Isolation, Culture, and Gene Transfer of Adult Canine Cardiac Myocytes -- Myofilament Protein Phosphorylation by PKC in Genetically Engineered Adult Cardiac Myocytes -- In Vivo Cardiac Gene Transfer -- Embryonic and Neonatal Cardiac Gene Transfer In Vivo -- Efficient Viral Gene Transfer to Rodent Hearts In Vivo -- Direct Gene Transfer to the Adult Rodent Myocardium In Vivo -- Adenovirus-Mediated Gene Transfer to Cardiac Myocytes In Vivo Using Catheter-Based Procedures -- Coronary Perfusion Cocktails for In Vivo Gene Transfer -- Modification of In Vivo Cardiac Performance by Intracoronary Gene Transfer of ?-Adrenergic Receptor Signaling Components -- Protocols for Hemodynamic Assessment of Transgenic Mice In Vivo.
Keywords: Cardiology; Cardiology